Cancer gene mutations in congenital pulmonary airway malformation patients. Issue 1 (4th February 2019) - Hsu, Jacob Shujui; Zhang, Ruizhong; Yeung, Fanny; Tang, Clara S.M.; Wong, John K.L.; So, Man-Ting; Xia, Huimin; Sham, Pak; Tam, Paul K.; Li, Miaoxin; Wong, Kenneth K.Y.; Garcia-Barcelo, Maria-Mercè
Background: Newborns affected with congenital pulmonary airway malformations (CPAMs) may present with severe respiratory distress or remain asymptomatic. While surgical resection is the definitive treatment for symptomatic CPAMs, prophylactic elective surgery may be recommended for asymptomatic CPAMs owing to the risk of tumour development. However, the implementation of prophylactic surgery is quite controversial on the grounds that more evidence linking CPAMs and cancer is needed. The large gap in knowledge of CPAM pathogenesis results in uncertainties and controversies in disease management. As developmental genes control postnatal cell growth and contribute to cancer development, we hypothesised that CPAMs may be underlain by germline mutations in genes governing airways development. Methods: Sequencing of the exome of 19 patients and their unaffected parents. Results: A more than expected number of mutations in cancer genes (false discovery rate q-value <5.01×10 −5 ) was observed. The co-occurrence, in the same patient, of damaging variants in genes encoding interacting proteins is intriguing, the most striking being thyroglobulin ( TG ) and its receptor, megalin ( LRP2 ). Both genes are highly relevant in lung development and cancer. Conclusions: The overall excess of mutations in cancer genes may account for the reported association of CPAMs with carcinomas and provide some evidence to argue for prophylactic surgery by some surgeons. Congenital pulmonary airway malformation (CPAM) patients have more than expected numbers of damaging variants in genes involved in lung carcinoma; this may provide evidence for clinicians choosing to adopt prophylactic excision in CPAM http://ow.ly/h1AE30n4DIe